Investment of Czech Institutional Sectors in the Business Cycle - Lukáš Kučera (European Financial and Accounting Journal, 2014)
Paper deals with the analysis of investment in the business cycle. Analysis is based on available quarterly data for the Czech Republic since 1st quarter 1999 till 1st quarter 2014. It concludes that investment on the macroeconomic level is highly pro-cyclical component of demand, which fluctuates in the business cycle more than GDP. Investment of individual institutional sectors, which together forms investment of the national economy, behaves in the business cycle highly differentiated. Investment of households, for example, develops the same way as GDP and its volatility is quite low. Investment of government institutions, on the contrary, is strongly volatile, and in addition, develops slightly anti-cyclically. It applies therefore, that cyclical component of investment of the national economy is very heterogeneous.
Keywords: E22; E32; 650; Investment; Business cycle; Institutional sectors